Community Policing Strategy (Polmas) In The Implementation Of Bhabinkamtibmas Tasks As A Radical Detection Basis - Surajab Surajab (Magister of Law, Faculty of Law, Universitas Islam Sultan Agung, 2020)
The implementation of the Community Policing Strategy (POLMAS) in the implementation of BhabinKamtibmas duties as the basis for the detection of radical understanding, is very important in creating social security. This study aims to analyze the Polmas Strategy in the implementation of BhabinKamtibmas duties as the basis for the detection of radical understanding, potential constraints and problems related to the implementation of the Polmas Strategy in implementing the duties of BhabinKamtibmas as the basis for the detection of radical understanding. The method used in this research is normative legal research. Sources and data types use primary data and secondary data. The data collection method was done through literature study, while the data analysis method used qualitative analysis. The results showed that the implementation of the Community Police Strategy in the implementation of BhabinKamtibmas duties as the basis for the detection of radical ideology, namely BhabinKamtibmas carrying out door-to-door visits to all areas of its assignment, carrying out and assisting problem solving, organizing and securing activities the public, receive information about the occurrence of non-crime, provide guidance and guidance to the public or the community regarding issues of social security and police services. The obstacles faced are the developing police culture, young police officers, the idiom that police officers on the streets are better than police officers who work behind the desk, the accountability of the police in response to complaints and the dynamics that occur in society, limited human resources, welfare of police officers, 2 police car patrols, accountability command, structural rewards, community satisfaction with police performance, failure to integrate Police work with criminal detection. The problems faced are the public's negative perception of the police, low public awareness of environmental security, sociological diversity of society, ambiguity in people's attitudes, facilities and infrastructure.Keywords: Community Policing; Community Security; Radical Understanding.